How do you find f'(3) using the limit definition given #1/(x^2-1)#?

Answer 1

When asked to differentiate using the limit definition, use the formula #f'(x) = lim_(h ->0) (f(x + h) - f(x))/h#.

Let the function be #f(x)#:
#f'(x) = lim_(h ->0) (f(x + h) - f(x))/h#
#f'(x) = lim_(h->0) (1/((x + h)^2 - 1) - 1/(x^2 - 1))/h#
#f'(x) = lim_(h->0) (1/(x^2 + 2xh + h^2 - 1) - 1/(x^2 - 1))/h#
#f'(x) = lim_(h->0) ((x^2 - 1 - (x^2 + 2xh + h^2 - 1))/((x^2 - 1)(x^2 + 2xh + h^2 - 1)))/h#
#f'(x) = lim_(h->0) ((x^2 - 1-x^2 - 2xh-h^2+ 1)/((x^2 - 1)(x^2+ 2xh + h^2 - 1)))/h#
#f'(x) = lim_(h->0) (-2xh + h^2)/(h(x^4 + 2x^3h + x^2h^2 - x^2 - x^2-2xh-h^2 + 1))#
#f'(x) = lim_(h->0) (cancel(h)(-2x + h))/(cancel(h)(x^4 + 2x^3h + x^2h^2+ 2xh + h^2 + 1 - 2x^2)#

Substituting:

#f'(x) = (-2x + 0)/(x^4 + 2x^3(0) + x^2(0)^2 + 2x(0) + 0^2 + 1 - 2x^2)#
#f'(x) = -(2x)/(x^4 - 2x^2+ 1)#
Hence, the derivative of #f(x) = 1/(x^2 - 1)# is #f'(x) = -(2x)/(x^4 - 2x^2 + 1)#. All that we have left to do is plug in #x = 3# into our derivative:
#f'(3) = -(2 xx 3)/(3^4 - 2(3)^2 + 1)#
#f'(3) = -6/(81 - 18 + 1)#
#f'(3) = -6/(64)#
#f'(3) = -3/32#
In summary, when #f'(3)# is evaluated inside the derivative of #f(x) = 1/(x^2 - 1)#, a result of #-3/32# is obtained.

Hopefully this helps!

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find ( f'(3) ) using the limit definition, we start with the function ( f(x) = \frac{1}{x^2 - 1} ) and use the definition of the derivative:

[ f'(a) = \lim_{h \to 0} \frac{f(a + h) - f(a)}{h} ]

In this case, ( a = 3 ), so we have:

[ f'(3) = \lim_{h \to 0} \frac{f(3 + h) - f(3)}{h} ]

Now, let's plug in the function ( f(x) = \frac{1}{x^2 - 1} ) and ( a = 3 ) into the limit definition:

[ f'(3) = \lim_{h \to 0} \frac{\frac{1}{(3 + h)^2 - 1} - \frac{1}{3^2 - 1}}{h} ]

Simplify the expression inside the limit:

[ f'(3) = \lim_{h \to 0} \frac{\frac{1}{9 + 6h + h^2 - 1} - \frac{1}{8}}{h} ]

[ f'(3) = \lim_{h \to 0} \frac{\frac{1}{8 + 6h + h^2} - \frac{1}{8}}{h} ]

Combine the fractions under the same denominator:

[ f'(3) = \lim_{h \to 0} \frac{\frac{8 - (8 + 6h + h^2)}{8(8 + 6h + h^2)}}{h} ]

[ f'(3) = \lim_{h \to 0} \frac{\frac{-6h - h^2}{8(8 + 6h + h^2)}}{h} ]

Now simplify and factor out ( h ) from the numerator:

[ f'(3) = \lim_{h \to 0} \frac{-6 - h}{8(8 + 6h + h^2)} ]

[ f'(3) = \frac{-6}{8(8)} ]

[ f'(3) = \frac{-6}{64} ]

[ f'(3) = -\frac{3}{32} ]

So, ( f'(3) = -\frac{3}{32} ) using the limit definition.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7